Protective effect of Vitamin E against Glyphosate-induced Reproductive failure in Female Rats - Parastoo Heidari; Farah Farokhi; Gholamreza Najafi; Abbas Sadeghi (Fasa University of Medical Sciences, 2021)
Background & Objective: The glyphosate-based herbicide has a prominent role in the toxic mechanism in living systems. Previous studies have shown that vitamin E can have a protective effect on cells against oxidative damage. This study aimed to evaluate the protective effect of vitamin E against the toxic potential of glyphosate (Gly) in the reproductive system of female rats. Materials & Methods: In this experimental study, 30 female Wistar rats were randomly divided into five groups (n=6), including control, glyphosate (50 mg/kg per day), glyphosate (500 mg/kg per day), glyphosate (50 mg/kg per day) + vitamin E (50 mg/kg per day), and glyphosate (500 mg/kg per day) + vitamin E (50 mg/kg per day). Glyphosate was administered orally, and vitamin E was administered by intraperitoneal injection. After 35 days, rats were euthanized, and embryo development, malondialdehyde (MDA) concentration, and catalase (CAT) activity were examined. Moreover, the levels of estrogen and progesterone were measured in the serum. Results were analyzed by SPSS software using one-way ANOVA and Tukey's post hoc test. Results: The glyphosate significantly decreased the percentages of fertilization, two-cell embryos, blastocysts, estrogen, and progesterone level as well as catalase activity and significantly increased MDA level in glyphosate-treated rats in comparison with controls (p<0.05). However, the results showed that vitamin E can reduce the toxicity of glyphosate administration in the mentioned parameters (p> 0.05). Conclusion: These results have shown that vitamin E can provide the antioxidant defense with potent preventive activity against glyphosate-induced reproductive toxicities.